Saudi nurses' perceptions of nursing as an occupational choice: a qualitative interview study - Gazzaz, Lamya Asaad (2009)
Background: Saudi Arabia has always been dependent on non-Saudi nurses. However, the recruitment of these nurses has been challenged by the consequences of the first Gulf War of 1991 and the political unrest in the Middle East ever since. Moreover, the annual supply of Saudi nursing graduates has been insufficient in meeting the demands of the expanding healthcare services. Indeed, Saudi nurses make less than 30% of the total nursing workforce Kingdom wide. The Saudi literature links the shortage in Saudi nurses to socio-cultural factors found to influence the prevailing negative images and perceived low status of nursing. Hence, I have developed a personal interest to explore the impact of prevalent images and perceived status of nursing on the Saudi nurses’ perceptions of nursing as an occupational choice. The reviewed literature guided the development of a framework for my study using six concepts.